A Goal Programming Model For Facility Location Planning - Basholli, Albina; Kedhi, Vasillaq; Cangonji, Alisa (European Scientific Journal, ESJ, 2016)
The aim of this paper is to apply Goal Programming in facility location. The feasibility project of a project idea on building an economic object is a defining moment in the decision making of the party that is investing on a certain project. Generally, the feasibility is done based on the global data extracted by the practical experience of building and functioning of similar existing object. However, it is understandable that the accuracy of the feasibility results is increased when different points of view are used in combination with exact methods of calculation. In this aspect, it is important to predict the income from the use of the object’s capacities. This leads to an intermediary problem which consists in predicting the most result oriented use of the object’s capacities. If the use of these capacities can be mathematically modeled through optimization models, then the basis of the data for evaluating the feasibility of the object becomes clearer. In this study was considered the possibility of using a mathematical model for the basin used by a yacht harbor. As a result, it is shown that the optimal use of a basin by a yacht harbor can be modeled as an objective function problem, which according to previously known methods can turn into a mathematical programming problem.